Hydrodynamic effects in laser cutting of biological tissue phantoms. (November 2017) - Zhigarkov, V.S.; Yusupov, V.I.; Tsypina, S.I.; Bagratashvili, V.N.
Abstract: We study the thermal and transport processes that occur in the course of incision formation at the surface of a biological tissue phantom under the action of near-IR, moderate-power, continuous-wave laser radiation (λ = 1.94 μm) delivered by means of an optical fibre with an absorbing coating on its exit face. It is shown that in addition to the thermal effect, the laser-induced hydrodynamic effects caused by the explosive boiling of the interstitial water make a large contribution to the phantom destruction mechanism. These effects lead to the tissue rupture accompanied by the ejection of part of the fragmented substance from the site of laser impact and the formation of highly porous structure near the incision surface. We have found that the depth, the width and the relief of the laser incision wall in the case of using the optical fibre moving with a constant velocity, depend on the fibre tilt angle with respect to the phantom surface, as well as the direction of the fibre motion.